First, rewrite the expression as:
#((y * y) * (x^3 * x))^2#
Rewrite the two #y# and one #x# variables using this rule of exponents:
#a = a^color(red)(1)#
#((y^color(red)(1) * y^color(red)(1)) * (x^3 * x^color(red)(1)))^2#
Now, use this rule of exponents to multiply the #x# and the #y# variables:
#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#
#((y^color(red)(1) * y^color(blue)(1)) * (x^color(red)(3) * x^color(blue)(1)))^2 => #
#(y^(color(red)(1)+color(blue)(1)) * x^(color(red)(3)+color(blue)(1)))^2 => #
#(y^2x^4)^2#
Now, use this rule of exponents to complete the simplification:
#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(y^color(red)(2)x^color(red)(4))^color(blue)(2) =>#
#y^(color(red)(2) xx color(blue)(2))x^(color(red)(4) xx color(blue)(2)) =>#
#y^4x^8# or #x^8y^4#